A second life for wine grapes: Discovering potentially bioactive oligosaccharides and phenolics in chardonnay marc and its processing fractions. (June 2021) - Sinrod, Amanda J.G.; Li, Xueqi; Bhattacharya, Mrittika; Paviani, Bruna; Wang, Selina C.; Barile, Daniela
Abstract: Chardonnay marc (pomace), an agricultural waste product, has demonstrated significant potential health benefits in previous studies. This study represents the first comprehensive chemical characterization of chardonnay marc, its seed and seedless fractions, and a seed extract to uncover the bioactive compounds inducing their observed health benefits. Chardonnay marc and its processing fractions' gross composition (i.e. protein, lignin, fat, carbohydrates, polysaccharides), phenolic contents, and oligosaccharide profiles were determined. The chardonnay seeds contained higher quantities of protein, fat, and polysaccharides than the seedless marc while the seedless marc contained more total carbohydrates and sugars. All samples had abundant phenolics with the seed extract being the most concentrated (34.72 ± 0.13 mg/g). (−)-Gallocatechin was the most abundant phenolic in the marc (1.4905 ± 0.0393 mg/g) and seedless marc (0.94 ± 0.04 mg/g), and (−)-epicatechin was the most concentrated phenolic in the seeds (9.4093 ± 0.1018 mg/g) and seed extract (14.22 ± 0.09 mg/g). Thirty-six distinct oligosaccharides were discovered between the four samples with three to nine degrees of polymerization and eleven distinct monosaccharide subunits. Overlap existed between the samples' oligosaccharides with six of the same hexose and hexose-pentose oligosaccharides present in all. Each sample, however, had a distinct oligosaccharide profile such as with eight oligosaccharides unique to the seed extract. Highlights: Composition analysis of chardonnay marc and its seed and seedless components. Phenolics and oligosaccharides differ between chardonnay seeds and seedless marc. All chardonnay marc fractions contain multiple, diverse oligosaccharides. Seedless chardonnay marc oligosaccharides are built from eleven monosaccharides. Subcritical water extraction increases phenolic content and oligosaccharide diversity.